Improving the Efficiency of Transverse Magnetic Polarized Emission from AlGaN Based LEDs by Using Nanowire Photonic Crystal - Xianhe Liu; Kishwar Mashooq; Thomas Szkopek; Zetian Mi (IEEE Photonics Journal)
AlGaN-based deep ultraviolet (UV) light-emitting diodes (LEDs) are attractive for a wide range of applications. To date, however, the best reported external quantum efficiency (EQE) for LEDs operating in the wavelength range of ∼240 nm is well below 1%. In this paper, we have performed detailed studies of the EQE of AlGaN nanowire photonic crystal LEDs in this wavelength range by finite-difference time-domain simulation. By coupling in-plane emission to vertical emission, light-extraction efficiency (LEE) over 90% can, in principle, be expected from the device top surface for transverse magnetic polarized photons that was not previously possible in conventional planar quantum well devices. Taken into account practical limitations including the absorptive p-Al(Ga)N contact and the presence of metal contact grid, LEE in the range of 30–40% is also expected. Moreover, due to the Purcell effect, the radiative recombination rate and, therefore, internal quantum efficiency (IQE) can be significantly modified in nanowire photonic crystal structures. We have established the design principles and ultimate efficiency limit of AlGaN nanowire photonic crystal LEDs: For AlGaN LEDs with very high IQE, EQE >70% can, in principle, be expected by operating near the Γ point of nanowire photonic crystals, whereas for structures with relatively low IQE it is preferred to operate near the M point to enhance the IQE while maintaining reasonably high LEE.